IMPLEMENTASI GAME THEORY DALAM PENENTUAN STRATEGI BERSAING PADA PRODUK SMARTPHONE - Ma'rifah, Diana (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2018)
AbstractThe purpose of this study is to analyze competitive strategy of smartphone company. Questionnaires were distributed to 100 students of STIE Putra Bangsa Kebumen. The aims of the questionnaires were to collect the data of students smartphone brand and the reason why they choose it. The data processing found that Xiaomi and Samsung are the most smartphone brands used by students. To determine the optimal strategy for both companies is analyzed using game theory. The results of this study are Xiaomi using price strategy and Samsung using quality product strategy.Keywords: smarthphone, game theory, competitive strategy.